Cathode active material for lithium secondary battery, and lithium secondary batterty comprising same
A bimodal lithium iron phosphate cathode active material mixture addresses conductivity and breakage issues, enhancing electrochemical performance and stability in lithium secondary batteries.
Patent Information
- Application Number
- KR1020250132883
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-10-27
AI Technical Summary
Conventional lithium iron phosphate cathode active materials suffer from low ionic and electronic conductivity, leading to reduced energy density and particle breakage during electrode rolling, which impairs electrochemical properties and composite density.
A bimodal cathode active material composed of a mixture of lithium iron phosphate coarse and fine particles, controlled within specific size and density ranges, to prevent particle breakage and enhance electrochemical performance.
The bimodal mixture improves charge/discharge capacity and reduces particle breakage, resulting in a lithium secondary battery with enhanced electrochemical characteristics and stability.
Smart Images

Figure 112025106286307-PAT00007_ABST
Abstract
Description
Technology Field
[0001] The present embodiments relate to a positive electrode active material for a lithium secondary battery and a lithium secondary battery containing the same. Background Technology
[0002] As the electric vehicle market becomes fully active, the market for cathodes, which account for more than 40% of the cost of lithium-ion batteries, is also growing rapidly every year. Automobiles are classified into six segments based on their overall length: Segment A for vehicles under 3,500mm and Segment F for vehicles over 5,000mm. Accordingly, electric vehicles using batteries utilize different cathodes to match their grade and driving range. For electric vehicles with a driving range of over 600km on a single charge, high-energy-density lithium-ion batteries are required, necessitating the use of high-nickel NCM cathode active materials, while Mid-Ni NCM materials are used for vehicles with a range of around 400km. However, for electric vehicles that do not require a high driving range and are relatively inexpensive, using materials that offer high safety and excellent lifespan, even if they do not have high energy density, is advantageous in terms of cost.
[0003] Lithium iron phosphate (LiFePO4) cathode is an olivine-based material composed of FeO6 octahedral sites and PO4 octahedral sites, in which lithium ions are deinserted and inserted through a one-dimensional pathway. This material has a cost advantage as its main composition consists of Li, Fe, and P, and the cost of metal minerals is lower compared to NCA or NCM materials that mainly use Ni and Co. Additionally, due to strong PO bonds, the structure is stable, and there is no oxygen dissociation at high temperatures during charging, which gives it the advantage of excellent thermal stability.
[0004] However, due to the low ionic and electronic conductivity of conventional lithium iron phosphate cathode active materials, nano-sized particles and carbon coating are essential. Consequently, energy density decreases due to low particle density and increased specific surface area. Furthermore, lithium iron phosphate cathodes in the form of secondary particles suffer from delamination caused by particle breakage during electrode rolling, which lowers rolling strength; thus, there is a problem of reduced electrode rate characteristics as well as composite density. Therefore, research was conducted on a lithium iron phosphate cathode active material capable of overcoming these disadvantages, and the present invention was completed. The problem to be solved
[0005] In this embodiment, we aim to provide a bimodal cathode active material for a lithium secondary battery that uses a mixture of lithium iron phosphate coarse particles and lithium iron phosphate small particles, which prevents particle breakage during rolling and improves density to enhance electrochemical properties, and a lithium secondary battery containing the same. means of solving the problem
[0006] A positive electrode active material for a lithium secondary battery according to one embodiment may be a positive electrode active material for a lithium secondary battery satisfying Formula 1 below, in a bimodal form using a mixture of lithium iron phosphate alleles and lithium iron phosphate subparticles:
[0007] [Equation 1]
[0008] 10% ≤ 100 * (FE) / E ≤ 30%
[0009] In the above Equation 1,
[0010] E is the positive active material at 4 ton / cm² 2 It refers to D1 before compression, and
[0011] F is the positive active material at 4 ton / cm² 2 It means D1 after compression.
[0012] A positive electrode for a lithium secondary battery according to another embodiment may include a positive electrode active material manufactured according to one embodiment.
[0013] A lithium secondary battery according to another embodiment may include a positive electrode for the lithium secondary battery according to one embodiment. Effects of the invention
[0014] According to the present embodiment, the positive electrode active material for a lithium secondary battery uses a mixture of lithium iron phosphate coarse particles and lithium iron phosphate fine particles to ensure that particle size-related parameters are within a specific range, thereby preventing particle breakage during rolling and improving electrochemical properties.
[0015] Accordingly, the performance of the lithium secondary battery manufactured as in the present embodiment can be improved. Brief explanation of the drawing
[0016] Figure 1 is an SEM image of the surface of the positive electrode active material prepared in Comparative Example 1, magnified 5,000 times. Figure 2 shows the surface of the positive electrode active material prepared in Comparative Example 1 20,000 times This is an SEM image measured under magnification. Figure 3 shows the surface of the positive electrode active material prepared in Comparative Example 4 5,000 times This is an SEM image measured under magnification. Figure 4 shows the surface of the positive electrode active material prepared in Comparative Example 4 20,000 times This is an SEM image measured under magnification. Figure 5 is a graph of particle size analysis performed on the cathode active material of Comparative Example 1. Figure 6 is a graph of particle size analysis performed on the positive electrode active material of Comparative Example 2. Figure 7 is a graph of particle size analysis performed on the positive electrode active material of Example 1. Figure 8 is a graph of particle size analysis performed on the positive electrode active material of Example 2. Figure 9 is a graph of particle size analysis performed on the positive electrode active material of Example 3. Figure 10 is a graph of particle size analysis performed on the positive electrode active material of Comparative Example 3. Figure 11 is a graph of particle size analysis performed on the positive electrode active material of Comparative Example 4. FIG. 12 shows the charge / discharge test results (@discharge rate 1C, 25℃) measured for electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4. FIG. 13 shows the charge / discharge test results (@discharge rate 10C, 25℃) measured for electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 4. Specific details for implementing the invention
[0017] Terms such as first, second, and third are used to describe various parts, components, regions, layers, and / or sections, but are not limited thereto. These terms are used solely to distinguish one part, component, region, layer, or section from another part, component, region, layer, or section. Accordingly, the first part, component, region, layer, or section described below may be referred to as the second part, component, region, layer, or section without departing from the scope of the present invention.
[0018] The technical terms used herein are for the reference of specific embodiments only and are not intended to limit the invention. The singular forms used herein include plural forms unless phrases clearly indicate otherwise. As used in the specification, the meaning of "comprising" specifies certain characteristics, areas, integers, steps, actions, elements, and / or components, and does not exclude the presence or addition of other characteristics, areas, integers, steps, actions, elements, and / or components.
[0019] When it is stated that one part is "above" or "on" another part, it may be directly above or on the other part, or other parts may be involved in between. In contrast, when it is stated that one part is "directly above" another part, no other parts are interposed in between.
[0020] Unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as generally understood by those skilled in the art to which this invention pertains. Terms defined in commonly used dictionaries are further interpreted to have meanings consistent with relevant technical literature and the present disclosure, and are not interpreted in an ideal or highly formal sense unless otherwise defined.
[0021] Also, unless otherwise specified, % means weight %, and 1 ppm is 0.0001 weight %.
[0022] In this specification, the term “combination(s) of these” described in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including any one or more selected from the group consisting of said components.
[0023] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.
[0025] Cathode active material for lithium secondary batteries
[0026] As mentioned above, conventional lithium iron phosphate cathode active materials have a problem in that their electrochemical properties deteriorate because their density cannot be increased due to reduced energy density and particle breakage occurring during rolling.
[0027] However, in this embodiment, this problem was solved by using a mixture of lithium iron phosphate coarse particles and lithium iron phosphate small particles and controlling the particle size characteristics of the cathode active material through an appropriate mixing ratio.
[0028] Specifically, the positive electrode active material for a lithium secondary battery according to one embodiment is in a bimodal form using a mixture of lithium iron phosphate covalents and lithium iron phosphate subparticles, and the positive electrode active material is 4 ton / cm² 2 The cathode active material for a lithium secondary battery may satisfy the following Equation 1 after compression, with an increase rate (%) of D1.
[0029] [Equation 1]
[0030] 10% ≤ 100 * (FE) / E ≤ 30%
[0031] In the above Equation 1,
[0032] E is the positive active material at 4 ton / cm² 2 It refers to D1 before compression, and
[0033] F is the positive active material at 4 ton / cm² 2 It means D1 after compression.
[0034] If an anode exceeding or falling below the range of Equation 1 above is used, the electrochemical properties may not be excellent, such as the charge / discharge capacity being impaired due to fine particles.
[0035] Particle size analysis can be performed as described above. D1 refers to the particle size corresponding to the 1% region in the particle size distribution graph, and the change in the size of fine particles can be confirmed through the D1 increase rate. In this case, fine particles may refer to active material particles that are completely crushed into a primary particle form during the crushing process of active material or coarse particles having a particle size of less than or equal to a secondary particle form according to an embodiment of the present invention.
[0036] At this time, the above E (positive active material at 4 ton / cm 2Before compression, D1) may be 0.50 to 1.00 μm, and specifically, 0.60 to 0.90 μm, 0.65 to 0.85 μm, or 0.65 to 0.75 μm.
[0037] At this time, the above F (positive active material is 4 ton / cm 2 After compression, D1) may be 0.70 to 1.20 μm, specifically 0.75 to 1.10 μm, or 0.80 to 1.00 μm.
[0038] When the positive electrode active material according to the present embodiment satisfies one or more of the ranges listed above, a lithium secondary battery with excellent electrochemical characteristics, such as charge / discharge capacity, can be realized. In addition, since particle breakage during the rolling process can also be suppressed, it has a very advantageous effect.
[0039] In this embodiment, the positive electrode active material is 4 ton / cm² 2 The cathode active material for a lithium secondary battery may satisfy the following Equation 2, wherein the reduction rate (%) of the particle size distribution ratio of 1.3 μm or less after compression is 1.3 μm or less.
[0040] [Equation 2]
[0041] 30% ≤ 100 * (CD) / C ≤ 80%
[0042] In Equation 2 above, C represents the positive active material at 4 ton / cm² 2 It refers to the percentage of particle size distribution of 1.3 μm or smaller before compression, and D represents the cathode active material at 4 ton / cm² 2 It refers to the particle size distribution ratio (%) of 1.3 μm or smaller after compression. More specifically, the reduction rate (%) of the particle size distribution ratio of 1.3 μm or smaller may be 35 to 75%, 40 to 70%, or 50 to 70%.
[0043] If a positive active material is used that exceeds or falls below the range of Equation 2 above, the electrochemical properties may not be excellent, such as the charge / discharge capacity being impaired due to fine particles.
[0044] At this time, a wet analysis method or a dry analysis method may be used to determine the particle size distribution ratio, and preferably, a wet analysis method may be used. When using a wet analysis method, a dispersion solvent may be used, and DI water may be used as the dispersion solvent, and a dispersant may be further included. The concentration of the dispersant used may be 5 to 15 weight%, and the type of dispersant may be sodium hexametaphosphate, but is not limited thereto.
[0045] At this time, the above C (positive active material is 4 ton / cm 2 The particle size distribution ratio (%) of 1.3 μm or smaller before compression may be 3.5 to 10%, 4 to 9%, or 4.5 to 8%.
[0046] At this time, the above D (positive active material at 4 ton / cm 2 After compression, the particle size distribution ratio (%) of 1.3 μm or smaller may be 1 to 8%, 1.7 to 5%, or 2 to 3.5%.
[0047] In this embodiment, the average particle size (D50) of the lithium iron phosphate coarse is a secondary particle with a diameter of 7 to 12 μm, and the average particle size (D50) of the lithium iron phosphate sub-particle is a secondary particle with a diameter of 1.0 to 1.5 μm.
[0048] In this case, the secondary particle refers to a particle formed by the aggregation of several to hundreds of primary particles. Specifically, the above-mentioned allele may be a secondary particle formed by the aggregation of tens to hundreds of primary particles, and the above-mentioned elementary particle may be a secondary particle formed by the aggregation of several to tens of primary particles.
[0049] In this embodiment, the mixing weight ratio of lithium iron phosphate coarse particles to lithium iron phosphate small particles may be 80:20 to 60:40.
[0050] In this embodiment, the lithium iron phosphate allele and the lithium iron phosphate subparticle may each independently be a positive electrode active material for a lithium secondary battery, which is a compound represented by the following chemical formula 1.
[0051] [Chemical Formula 1]
[0052] Li 1+a Fe 1-x M x (PO 4-b )X b
[0053] In the above chemical formula 1, M comprises one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and X comprises one or more elements selected from the group consisting of F, S, and N, and a, b, and x are each -0.5≤a≤0.5, 0≤b≤0.1, and 0≤x≤0.5.
[0054] At this time, the lithium iron phosphate covalents and the lithium iron phosphate subparticles may have the same composition. Specifically, the lithium iron phosphate subparticles may be manufactured by crushing the lithium iron phosphate covalents.
[0056] cathode for lithium secondary batteries
[0057] In this embodiment, the aforementioned problem was solved by using a mixture of lithium iron phosphate coarse particles and lithium iron phosphate fine particles and controlling the ratio of the composite density to the pellet density through an appropriate mixing ratio.
[0058] Specifically, a positive electrode for a lithium secondary battery according to one embodiment may include a bimodal type positive electrode active material that uses a mixture of lithium iron phosphate covalents and lithium iron phosphate subparticles, and may be a positive electrode for a lithium secondary battery satisfying Formula 3 below.
[0059] [Equation 3]
[0060] 0.995 ≤ B / A ≤ 1.020
[0061] In Equation 3 above, A is the positive active material at 4 ton / cm 2 B represents the pellet density (g / cc) of the pellet compressed by the above, and B represents the composite density (g / cc) of the anode containing the above anode active material. More specifically, B / A (density ratio of composite density to pellet density) may be 1.000 to 1.015, or 1.004 to 1.013.
[0062] If an anode exceeding or falling below the range of Equation 3 above is used, the electrochemical characteristics may not be excellent, such as impaired charge / discharge capacity.
[0063] At this time, the pellet density may be 2.23 g / cc or higher, and specifically, 2.23 to 2.35 g / cc, 2.23 to 2.30 g / cc, or 2.23 to 2.29 g / cc.
[0064] At this time, the density of the composite may be 2.23 g / cc or higher, and specifically, it may be 2.23 to 2.35 g / cc, 2.24 to 2.30 g / cc, or 2.25 to 2.29 g / cc. The electrode composite, which is the subject of the measurement of the composite density, may include a positive active material, a conductive material, and a binder, and the composite density is weight per area (g / cm²). 2 It can be calculated by dividing the thickness (cm) of the electrode mixture excluding the current collector by ).
[0065] When the above density ratio range is satisfied, the degree of particle breakage during the rolling process of the anode or the charge / discharge capacity of the anode can be improved, as in the present embodiment.
[0066] Specifically, the anode described above may include a current collector and an anode active material layer located on one side of the current collector.
[0067] The above current collector may be, for example, made of stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc.
[0068] Meanwhile, the above positive active material layer may include a binder and a conductive material.
[0069] At this time, the binder serves to improve adhesion between positive active material particles and adhesion between the positive active material and the positive current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof. One of these alone or a mixture of two or more may be used, but is not limited thereto. The binder may be included in an amount of 1 to 30 weight% based on the total weight of the positive active material layer.
[0070] In addition, the conductive material is used to impart conductivity to the electrode, and in the battery being constructed, it may be used without special limitations as long as it possesses electronic conductivity without causing chemical changes. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used, but is not limited thereto. The conductive material may typically be included in an amount of 1 to 30 weight% relative to the total weight of the positive electrode active material layer.
[0071] The above anode can be manufactured according to a conventional anode manufacturing method, except that it is manufactured to correspond to the density ratio range.
[0073] Specifically, the anode may be manufactured by applying a composition for forming an anode active material layer, which optionally includes a binder, a conductive material, or a solvent as needed, onto an anode current collector, followed by drying and rolling. At this time, the types and contents of the anode active material, binder, and conductive material are as described above.
[0074] The above solvent may be a solvent commonly used in the relevant technical field, such as dimethylsulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one of these alone or a mixture of two or more may be used. The amount of the above solvent used is sufficient if it has a viscosity that allows for the dissolution or dispersion of the anode active material, conductive material, and binder, taking into account the coating thickness of the slurry and the manufacturing yield, and subsequently provides excellent thickness uniformity when coated for anode manufacturing.
[0075] Alternatively, the anode may be manufactured by casting a composition for forming an anode active material layer onto a separate support, and then laminating the film obtained by peeling off from the support onto an anode current collector.
[0077] lithium secondary battery
[0078] In another embodiment, a lithium secondary battery including the anode is provided.
[0079] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode positioned opposite to the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is as described above. Additionally, the lithium secondary battery may optionally further include a battery container housing an electrode assembly comprising the positive electrode, the negative electrode, and the separator, and a sealing member for sealing the battery container.
[0080] In the above lithium secondary battery, the negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0081] The above-mentioned negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. In addition, the above-mentioned negative current collector may typically have a thickness of 3 to 500 μm, and, similar to the positive current collector, fine irregularities may be formed on the surface of the current collector to strengthen the bonding strength of the negative active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0082] The above-mentioned cathode active material layer may optionally include a binder and a conductive material together with the cathode active material. The above-mentioned cathode active material layer may be manufactured, as an example, by applying a composition for forming a cathode active material layer, comprising a cathode active material and optionally a binder and a conductive material, onto a cathode current collector and drying it, or by casting the composition for forming a cathode onto a separate support and then laminating the film obtained by peeling it off from the support onto a cathode current collector.
[0083] As the above-mentioned negative electrode active material, a compound capable of reversible intercalation and deintercalation of lithium may be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides capable of doping and dedoping lithium, such as SiOβ (0 ≤ β ≤ 2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites comprising the above-mentioned metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or more of these may be used. Additionally, a metallic lithium thin film may be used as the above-mentioned negative electrode active material. Furthermore, the carbon material may include both low-crystallinity carbon and high-crystallinity carbon. Representative examples of low-crystallinity carbon include soft carbon and hard carbon, while representative examples of high-crystallinity carbon include amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes.
[0084] The binder and conductive material mentioned above may be the same as those previously described in the anode.
[0085] Next, depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers thereof may be used, and a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator may also be used.
[0086] In addition, regarding the above lithium secondary battery, the electrolyte may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which are usable when manufacturing a lithium secondary battery, but is not limited to these.
[0087] Specifically, the organic liquid electrolyte may include an organic solvent and a lithium salt.
[0088] The above organic solvent may be used without special restrictions as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the above organic solvent may include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; and aromatic hydrocarbon-based solvents such as benzene and fluorobenzene. Carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having C2 to C20 structures and may include a double bond, a directional ring, or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among these, a carbonate-based solvent is preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate, etc.) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery, and a low-viscosity linear carbonate-based compound (e.g., ethylmethyl carbonate, dimethyl carbonate or diethyl carbonate, etc.) is more preferred.In this case, using a mixture of cyclic carbonate and chain carbonate in a volume ratio of about 1:1 to about 1:9 can result in excellent performance of the electrolyte.
[0089] The above lithium salt can be used without special restrictions as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within the range of 0.1 to 2.0 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and allow lithium ions to move effectively.
[0090] As described above, since the lithium secondary battery including the positive electrode according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, it is useful in portable devices such as mobile phones, laptop computers, and digital cameras, as well as in the field of electric vehicles such as hybrid electric vehicles (HEVs).
[0092] Preferred embodiments and comparative examples of the present invention are described below. However, the following examples are merely preferred embodiments of the present invention, and the present invention is not limited to the following examples.
[0094] Example 1 - Preparation of a positive electrode active material and an electrode containing the same
[0095] Anhydrous FePO4 was processed once at 15,000 rpm using a rotary mill before use. FePO4 228.51 g, Li2CO3 57.66 g, C6H 12O619.63g and C6H8O73.71g were mixed with 700g of ultrapure water and ground in a bead mill at 3500 rpm for 2 hours (using 100–120g of 0.3 mm zirconia beads, NETZSCH MINISERIES model).
[0096] The mixed slurry obtained after wet bead milling as described above was spray-dried using a spray dryer (spray pressure: 1.5 bar, main chamber temperature: 250 degrees, outlet temperature: 100 degrees).
[0097] 30g of spray-dried product obtained by spray drying was placed in an alumina saga and calcined under a nitrogen atmosphere (calcination temperature: 670°C, calcination holding time: 6 hours, heating rate: 5°C / min, nitrogen flow rate: 0.6 L / min, oxygen removed by vacuuming the inside of the furnace and then purging with nitrogen prior to calcination).
[0098] Afterwards, the LFP sintered product was fed into a 4-inch jet-mill at a speed of 20 g / hr and ground with an ejector pressure setting of 3 bar to produce fine-particle LFP. Hereinafter, the LFP sintered product that was not ground is referred to as large-particle LFP.
[0099] Allyl LFP was mixed with elementary LFP in an 80:20 ratio and dry-mixed for 6 minutes using a co-rotating mixer.
[0100] Afterwards, an electrode slurry was prepared by adding 4.3g of N-methyl-2-pyrrolidone (NMP) to 4.5g of LFP, 0.25g of SuperP, and 3.125g of PVDF 8wt.% (product name: KF7208), which were mixed with large and small particles as described above.
[0101] The above slurry was coated onto an electrode using a doctor blade and dried at 130°C for 2 hours. Rolling was performed to a height of 0.03 mm. The anode loading amount was approximately 10-11 mg / cm², and the weight per unit area of the fabricated coin half-cell electrode was 11.23 g / cm². 2 The thickness was 50 μm, and the density of the mixture was 2.25 g / cc.
[0103] Examples 2 to 3 and Comparative Examples 1 to 4
[0104] A positive electrode active material and an electrode containing the same were prepared in the same manner as in Example 1, except that dry mixing was performed by adjusting the mixing ratio of allotropic LFP to small LFP particles. The specific mixing ratios are as listed in Table 1. For reference, Comparative Example 1 consists only of allotropic LFP, and Comparative Example 4 consists only of small LFP particles.
[0105] Fig. 1 is a Scanning Electron Microscopy (SEM) image of the surface of a coarse-shaped LFP cathode active material, which is an LFP calcined product that has not undergone grinding, magnified 5,000 times, and Fig. 2 is the same surface of the coarse-shaped LFP cathode active material magnified 20,000 times This is an magnified SEM image. Through this image, it can be confirmed that it is a secondary particle type.
[0106] In addition, Fig. 3 shows the surface of the fine particle LFP cathode active material subjected to grinding, 5,000 times This is an SEM image measured at magnification, and Fig. 4 shows the surface of the same microparticle LFP cathode active material magnified 20,000 times. This is an magnified SEM image. Through this image, it can be confirmed that it is a secondary particle type.
[0107] Referring to Figures 1 and 2, it can be seen that the LFP sintered product that has not undergone grinding is a secondary particle formed by the aggregation of tens to hundreds of primary particles, and that the average particle size (D50) is 7 to 10 μm.
[0108] Meanwhile, referring to FIGS. 3 and 4, it can be confirmed that the LFP sintered product subjected to grinding consists of secondary particles formed by the aggregation of several to tens of primary particles, and that the average particle size (D50) is 1 to 1.5 μm. In other words, it can be confirmed that the particle size has been reduced through grinding.
[0110] Experimental Example 1: Measurement of Density of Pellet and Prepared Electrode
[0111] (1) Pellet density measurement
[0112] 1.2 g of LFP powder mixed with large and small particles prepared in the examples and comparative examples was used. For reference, Comparative Example 1 is an LFP powder composed only of large particles, and Comparative Example 4 is an LFP powder composed only of small particles.
[0113] 1.2 g of LFP powder prepared in each example and comparative example, with a cross-sectional area of 1.3 cm 2 Put into a pelletizer and 5.2 to 5.3 tons (approx. 4 tons / cm²) 2 After making pellets by compressing with a force of ), the pellet density was calculated. The results are listed in Table 1 below.
[0114] (2) Measurement of the density of the manufactured electrode
[0115] The electrodes prepared in the examples and comparative examples were used. The weight per unit area (g / cm²) of the electrode mixture (active material + conductive material + binder) 2 The density of the electrode mixture was calculated by dividing the thickness (cm) of the electrode mixture excluding the current collector by the current collector. The results are shown in Table 1 below.
[0116] division Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Comparative Example 3 Comparative Example 4 Allele:Subatomic particle mixing weight ratio 10:0 9:1 8:2 7:3 6:4 5:5 0:10 Pellet density [g / cc, A] 2.25 2.23 2.24 2.28 2.23 2.23 2.24 Composition density [g / cc, B] 2.08 2.21 2.25 2.29 2.26 2.28 2.29 Mixture Density / Pellet Density [B / A] 0.924 0.991 1.004 1.004 1.013 1.022 1.022
[0117] In Table 1 above, it can be seen that Comparative Examples 1 to 4 have a composite density / pellet density [B / A] of 0.991 or less or 1.022 or more, and Examples 1 to 3 have a composite density / pellet density of 0.995 to 1.020.
[0118] Experimental Example 2: Measurement of Anode Active Material Particle Size
[0119] 0.02 g of LFP powder mixed with large and small particles prepared in the examples and comparative examples was used. For reference, Comparative Example 1 is an LFP powder composed only of large particles, and Comparative Example 4 is an LFP powder composed only of small particles.
[0120] 0.02 g of each LFP powder prepared in the examples and comparative examples was added to a solution mixed with 5 mL of DI water and 1 mL of 10 wt.% dispersant, dispersed using a bath sonicator for 5 minutes, and then the particle size and change in particle size distribution were measured using a Malvern particle size analyzer at 4 ton / cm² 2 Measurements were taken before and after compression. The results can be seen in Figures 5 to 11.
[0121] In FIGS. 5 to 11, the solid line represents 4 ton / cm 2 Particle size distribution before compression (Before, B), the dotted line is 4 ton / cm 2 This shows the particle size distribution after compression (After, A). The graph shows 4 ton / cm 2 After compression, it can be confirmed that the particle size of the comparative example and the example generally increases due to the aggregation of particles.
[0122] 4 ton / cm 2 The reduction rate (%) of the particle size distribution ratio of 1.3 μm or less after compression is shown in Table 2 below, 4 ton / cm 2 The D1 increase rate after compression is shown in Table 3 below.
[0124] division Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Allele:Subatomic particle mixing weight ratio 10:0 9:1 8:2 7:3 6:4 4 ton / cm 2 Particle size distribution ratio of 1.3 μm or smaller before compression [%, C] 0.75 3.33 7.19 7.46 4.91 4 ton / cm 2 Particle size distribution ratio of 1.3 μm or smaller after compression [%, D] 1.60 2.43 3.20 2.60 2.09 Reduction rate of particle size distribution ratio of 1.3μm or less [%, (CD) / Cx100] -113.3 (increase) 27.0 55.5 65.1 57.4
[0125] In Table 2 above, the value of the reduction rate (%) of the particle size distribution ratio of 1.3 μm or less in Comparative Example 1 is negative at 4 ton / cm² 2 This means that the number of fine particles increased after compression, indicating that particle breakage occurred. In Comparative Example 2 and Examples 1 to 3, as the particles aggregated due to compression and the overall particle size increased, it can be confirmed that the distribution ratio of particles smaller than 1.3 μm decreased. In particular, the reduction rate (%) of the distribution ratio of particles smaller than 1.3 μm in Examples 1 to 3 decreased significantly by more than 30%, indicating that the number of fine particles was effectively reduced and particle breakage during compression was suppressed.
[0126] division Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Comparative Example 3 Comparative Example 4 Allele:Subatomic particle mixing weight ratio 10:0 9:1 8:2 7:3 6:4 5:5 0:10 4 ton / cm 2 D1 [μm, E] before compression 2.129 0.877 0.672 0.672 0.746 0.749 0.858 4 ton / cm 2 After compression, D1 [μm, F] 1.074 0.922 0.809 0.862 0.955 1.090 1.187 D1 Growth Rate [%, (FE) / Ex100] -49.6 (decrease) 5.1 20.4 28.3 28.0 45.5 38.3
[0127] D1 refers to the particle size corresponding to the 1% region in the particle size distribution graph, and the change in fine particle size can be confirmed through the D1 increase rate. In this case, fine particles may refer to active material particles that have been completely ground into primary particle forms during the grinding process of active materials having a particle size smaller than that of fine particles in the form of secondary particles according to the embodiments of the present invention, or coarse particles. In Table 3 above, the negative value of the D1 increase rate (%) for Comparative Example 1 is 4 ton / cm² 2 This means that the size of the fine particles decreased after compression. Through this, it can also be confirmed that the fine particles increased due to particle breakage caused by compression.
[0128] In Comparative Examples 2 to 4 and Examples 1 to 3, it can be confirmed that D1 increased as the particle size increased overall due to particle aggregation by compression.
[0129] In addition, it can be confirmed that the D1 increase rate (%) of Examples 1 to 3 corresponds to the range of 10 to 30%.
[0131] Experimental Example 3: Analysis of Electrochemical Performance According to Density Ratio or Active Material Particle Size
[0132] The electrochemical performance of electrodes containing active materials of examples and comparative examples having the characteristics of Tables 1 to 3 above was measured and is shown in Table 4 below.
[0133] Specifically, the coin-type half-cells manufactured in the examples and comparative examples were aged at room temperature (25°C) for 24 hours, and then a charge / discharge test was performed.
[0134] After one formation cycle (2.5–3.65 V) with 0.1 C charge and discharge, the charge rate was fixed at 0.1 C, and measurements were taken once each at discharge rates of 0.1, 1, and 10 C (2.7–3.65 V). At this time, the CC-CV charge mode was used (Charge step condition: fixed at 0.1 C, 0.05 C cut-off current). A 20-minute rest was taken immediately after the charge and discharge steps. The results of the experiment are listed in Table 4 below.
[0136] division Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Comparative Example 3 Comparative Example 4 Allele:Subatomic particle mixing weight ratio 10:0 9:1 8:2 7:3 6:4 5:5 0:10 0.1 C Discharge [mAh / g] 159.8 159.2 158.2 158.2 157.7 157.9 151.0 Initial efficiency [%] 99.0 99.2 99.0 98.9 98.9 98.7 98.5 1 C Discharge [mAh / g] 142.6 125.5 144.4 143.9 143.1 143.1 142.8 1 C / 0.1C capacity retention [%] 89.0 78.7 91.0 90.8 90.6 90.4 90.7 10 C Discharge [mAh / g] 82.5 3.4 106.4 104.4 103.5 99.0 91.8 10 C / 0.1C capacity retention [%] 51.5 2.1 67.1 65.8 65.5 62.6 58.4
[0137] Referring to Table 4, it can be seen that the charge / discharge characteristics of the electrode are excellent when mixed in a bimodal form compared to Comparative Examples 1 and 4, in which lithium iron phosphate large particles and lithium iron phosphate small particles were not mixed. When compared to Comparative Example 2, in which large particles and small particles were mixed at a weight ratio of large particles to small particles of 9:1, it can be seen that the 10 C discharge data has a significantly lower value in Comparative Example 2, while Examples 1 to 3 have a value of 100 mAh / g or higher.
[0138] In addition, it does not satisfy the preferred particle size characteristics according to the present invention and 4 ton / cm 2 Compared to Comparative Examples 1 to 4, in which the ratio of the composite density (g / cc) to the compressed pellet density (g / cc) is 0.991 or less or 1.022 or more, the present invention satisfies the preferred particle size characteristics and 4 ton / cm 2It can be confirmed that the charge / discharge characteristics of the electrodes of Examples 1 to 3, in which the ratio of the composite density (g / cc) to the compressed pellet density (g / cc) is 0.995 to 1.020, are significantly superior. Specifically, since Examples 1 to 3 have a capacity retention value of 65% or higher with a 10 C / 0.1 C capacity retention value, it can be confirmed that they have superior effects when compared to Comparative Examples 1 to 4.
[0139] Therefore, through a comparison of the examples and comparative examples, it can be confirmed that the positive electrode active material according to Examples 1 to 3 is electrochemically superior.
[0141] The present invention is not limited to the above embodiments and can be manufactured in various different forms, and those skilled in the art will understand that the invention can be implemented in other specific forms without changing the technical concept or essential features of the invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.
Claims
Claim 1 As a bimodal form using a mixture of lithium iron phosphate allotropes and lithium iron phosphate subparticles, the positive electrode active material is 4 ton / cm² 2 A positive electrode active material for a lithium secondary battery in which the growth rate (%) of D1 (particle size corresponding to the 1% region in the particle size distribution graph) after compression satisfies the following Equation 1: [Equation 1] 10% ≤ 100 * (FE) / E ≤ 30% In the above Equation 1, E is the positive electrode active material at 4 ton / cm² 2 It refers to D1 before compression, and F is the positive active material at 4 ton / cm² 2 It means D1 after compression. Claim 2 In claim 1, the above E (positive active material is 4 ton / cm 2 A positive electrode active material for a lithium secondary battery, wherein D1) is 0.50 to 1.00 μm before compression. Claim 3 In claim 1, the above F (positive active material at 4 ton / cm 2 A positive electrode active material for a lithium secondary battery, wherein D1) is 0.70 to 1.20 μm after compression. Claim 4 In claim 1, the positive active material is a positive active material at 4 ton / cm 2 A positive electrode active material for a lithium secondary battery, wherein the reduction rate (%) of the particle size distribution ratio of 1.3 μm or less after compression satisfies the following Equation 2: [Equation 2] 30% ≤ 100 * (CD) / C ≤ 80% In the above Equation 2, C is the positive electrode active material at 4 ton / cm² 2 It refers to the particle size distribution ratio (%) of 1.3μm or smaller before compression, and D represents the cathode active material at 4 ton / cm² 2 It refers to the particle size distribution ratio (%) of 1.3 μm or smaller after compression. Claim 5 In paragraph 4, the above C (positive active material is 4 ton / cm 2 A positive electrode active material for a lithium secondary battery, wherein the particle size distribution ratio (%) of 1.3 μm or smaller before compression is 3.5 to 10%. Claim 6 In paragraph 4, the above D (positive active material at 4 ton / cm 2 A positive electrode active material for a lithium secondary battery, wherein the particle size distribution ratio (%) of 1.3 μm or smaller after compression is 1 to 8%. Claim 7 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size (D50) of the lithium iron phosphate coarse is a secondary particle of 7 to 12 μm, and the average particle size (D50) of the lithium iron phosphate small particle is a secondary particle of 1.0 to 1.5 μm. Claim 8 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the mixing weight ratio of the lithium iron phosphate coarse particles to the lithium iron phosphate fine particles is 80:20 to 60:
40. Claim 9 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium iron phosphate allele and the lithium iron phosphate subparticle are each independently a compound represented by the following chemical formula 1: [Chemical Formula 1]Li 1+a Fe 1-x M x (PO 4-b )X b In the above chemical formula 1, M comprises one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and X comprises one or more elements selected from the group consisting of F, S, and N, and a, b, and x are each -0.5≤a≤0.5, 0≤b≤0.1, and 0≤x≤0.
5. Claim 10 A positive electrode active material for a lithium secondary battery, wherein, in claim 1, the lithium iron phosphate allele and the lithium iron phosphate subparticle have the same composition. Claim 11 A positive electrode for a lithium secondary battery comprising a positive electrode active material for a lithium secondary battery according to any one of claims 1 to 10. Claim 12 A lithium secondary battery comprising a positive electrode for a lithium secondary battery according to claim 11.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery and lithium secondary battery including the same
JP7254875B2
Lithium ion battery
KR1020140012008A
Positive electrode active material for lithium secondary battery, preparing method of the same, positive electrode and lithium secondary battery including the same
KR1020190041715A
Electrodes for secondary batteries and lithium-ion secondary batteries
KR1020210062009A
Positive electrode material for lithium secondary battery and preparing method of the same
KR1020210071612A
